2007
DOI: 10.1097/01.ogx.0000271111.20802.e0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality and Severe Morbidity Associated With Low-Risk Planned Cesarean Delivery Versus Planned Vaginal Delivery at Term

Abstract: C esarean delivery rates in industrialized countries continue to rise. 1,2 The rates vary widely by country, health care facility and delivering physician, partly because of differing perceptions by health care providers as well as by pregnant women of its benefits and risks. [3][4][5][6][7] The relative safety of cesarean delivery and its perceived advantages relative to vaginal delivery have resulted in a change in the perceived risk-benefit ratio, which has accelerated acceptance. 1,[4][5][6][7][8][9][10][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 22 publications
(45 reference statements)
5
119
0
11
Order By: Relevance
“…Caesarean section, especially those that are not medical justified, include a risk of maternal morbidity and mortality [30], as well as a risk of physical, emotional, and reproductive consequences for the mother and negative health outcomes for the child [31]. The growing rate of caesarean sections also has financial implications as the average cost of elective caesarean section is between 27-63% higher than vaginal delivery [32].…”
Section: Resultsmentioning
confidence: 98%
“…Caesarean section, especially those that are not medical justified, include a risk of maternal morbidity and mortality [30], as well as a risk of physical, emotional, and reproductive consequences for the mother and negative health outcomes for the child [31]. The growing rate of caesarean sections also has financial implications as the average cost of elective caesarean section is between 27-63% higher than vaginal delivery [32].…”
Section: Resultsmentioning
confidence: 98%
“…Sheiner et al [27] reported a cesarean delivery rate of 25.5% in pregnancies after restrictive gastric bypass. Obstetricians attending post-bariatric surgery patients need to be aware of hemoglobin levels at the end of pregnancy since blood loss is known to be higher during cesarean delivery than during vaginal delivery [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, where patients are fully informed, restrictions on treatment cannot be based on the risks to the individuals themselves. After all, women are allowed to choose elective caesarean section despite the increases in risks of haemorrhage, hysterectomy, and cardiac arrest [44]. 13 Restrictions to individual liberty can generally be justified only if there are harms to third parties [28, p. 26].…”
Section: Risk For Women?mentioning
confidence: 99%